Periodic Medical Checkup: Knowledge and Practice in a Community in South West Nigeria - Olayinka Stephen Ilesanmi; Bridget Omotoso; Faith Alele; Ibidun Amenkhienan (Universiti Kebangsaan Malaysia, 2015)
Introduction: Most individuals in Nigeria pay little attention to health issues and accord little or no priority to medical check-up. This study was conducted to determine the knowledge and practice of periodic medical check-up in south west Nigeria. Methods: A descriptive cross-sectional study was carried out among 231 respondents in Owo, Ondo State, South West Nigeria. A structured interviewer administered questionnaire was used and data was analyzed using SPSS version 21. Respondents with 2 and above positive response to questions on medical check-up were regarded as having it frequently. Association between categorical variables were explored using chi square, Level of significance was set at 5%. Results: The mean age of the respondents was 52.4±17.9 years, 60.2% were females and 80.6% were married. About 62% (144) have ever heard of periodic medical check-up, 79% (114) of those who have heard had ever had it done and only 48.2% among those who had ever done it had frequent medical check-up. A statistically significant proportion of respondents who were 60 years and above (54.8%) had frequent medical check-up compared to 23.1% of respondents who were less than or equal to 40 years (p=0.014). Conclusions: Effort is needed in ensuring that periodic medical check-up is encouraged. There is a need to study the factors associated with the uptake of medical check-up among the study population.